E-009 Pipeline embolization of vertebrobasilar aneurysms. (22nd July 2018) - Wallace, A; Kamran, M; Madaelil, T; Kayan, Y; Kansagra, A; Grossberg, J; Almandoz, J Delgado; Moran, C; Roy, A; Cross, D; Howard, B; Cawley, C; et al.
Abstract : Introduction: The Pipeline Embolization Device (PED) has greatly expanded the range of aneurysms amenable to endovascular treatment, including those with wide necks that incorporate branch vessels. Published occlusion rates of anterior circulation aneurysms treated with the PED typically exceed 85% 1–7 with morbidity rates of less than 7%. 7 8 Prompted by this success, the PED is being increasingly utilized for the off-label treatment of posterior circulation aneurysms with widely varying results. 9 10 The purpose of this study was to examine the procedural, clinical, and angiographic outcomes of patients with vertebrobasilar aneurysms treated with the PED. Methods: Retrospective review of the neurointerventional databases of three high-volume neurovascular centers was approved by respective institutional review boards to identify patients with vertebrobasilar aneurysms treated with the PED between 2012 and December 2016. Demographic, clinical, and angiographic data were collected from electronic medical records. Procedural details, including devices used and peri-procedural complications, were collected from operative reports. Preoperative digital subtraction angiography was reviewed to determine the morphological characteristics of treated aneurysms, including largest diameter in any dimension, location, shape, and incorporated branch vessels. Follow-up angiographic images were also reviewed for intra-PED stenosis and patency of branch vessels covered by the PED. Results: During the study period, 27 patients with 29 vertebrobasilar aneurysms underwent 28 treatments with the PED. The patients were 37% (10/27) men and 63% (17/27) women with a mean age of 53.3 years (range, 32–75 years), 44% (12/27) of whom were previous or current smokers. 74% (20/27) of patients were asymptomatic at presentation. Six of the remaining patients presented with subarachnoid hemorrhage (SAH; 22%, 6/27) and one patient presented with stroke related to thrombosis of brainstem perforators incorporated into the aneurysm (3.7%, 1/27). Aneurysm locations included the basilar trunk (41%, 12/29), basilar tip (7%, 2/29), vertebral artery (VA) proximal to the posterior inferior cerebellar artery (PICA; 10%, 3/29), VA at the PICA origin (10%, 3/29), and post-PICA VA (17%, 5/29). There were 15 saccular aneurysms (50%) with a mean size of 8.1 mm (range, 1.7–38 mm), 13 fusiform aneurysms (47%) with mean size of 11.8 mm (range, 4.3–34 mm) and length of 11.4 mm (range, 3.4–33), and one 2.9 mm blister aneurysm. The overall procedural complication rate was 18% (5/28), and the neurologic morbidity and mortality rate was 11% (3/28). Excluding aneurysms in patients who died, angiographic follow up was available for 96% (26/27) of patients. Mean duration of follow up was 12 months (range, 3–59 months). At last angiographic follow up, 67% (18/27) of aneurysms were completely occluded and 81% (22/27) were completely or near-completely occluded. A total of 36 branch vessels in 21 patients were covered by at least one PED. At last angiographic follow up, 8% (3/36) of covered branch vessels were occluded, none of which were symptomatic. Conclusion: Pipeline embolization of vertebrobasilar aneurysms is associated with a higher complication rate and lower occlusion rate compared with anterior circulation aneurysms, but may be a viable treatment option in select cases. Disclosures: A. Wallace: None. M. Kamran: None. T. Madaelil: None. Y. Kayan: 2; C; Medtronic, Penumbra, MicroVention. A. Kansagra: None. J. Grossberg: None. J. Delgado Almandoz: 2; C; Medtronic, Penumbra, Microvention, Accriva Diagnostics. C. Moran: 2; C; Medtronic. A. Roy: None. D. Cross: None. B. Howard: None. C. Cawley: None. J. Dion: None. T. CreveCoeur: None. J. Osbun: 1; C; MicroVention.